Application of Turmeric Extract Botanical Insecticide On Feeding Activity And Mortality Of Spodoptera Litura Larvae - Nurmaisah; Mellia Wasti Mau; Abdul Rahim (Talenta Publisher, 2023)
This research aimed to evaluate the effectiveness of turmeric extract as a botanical insecticide on the feeding activity and mortality of Spodoptera litura larvae. The method used in this study was a toxicity test using the leaf dip method. The experiment employed a completely randomized design with combinations of turmeric extract concentrations (0, 4, 8, 12, and 16 grams per liter of water) and instar types (1 and 2). The results showed that the application of turmeric extract on cabbage leaves reduced the feeding activity of instar 2 and 3 larvae. Meanwhile, the turmeric extract had an effect on the mortality of instar 2 and 3 larvae only at a concentration of 16%. The symptoms observed in the dead larvae were changes in color and body texture. The conclusion of this research is that 16% is the minimum effective concentration of turmeric extract on instar 2 and 3 S. litura larvae. This study should be continued on other instar types at the field scale.